From Planning To Reality: Managing Scout Extracurriculars – A Case Study - Erinda, Hayyu; Imron, Ali; Sunarni, Sunarni (Universitas Negeri Malang, 2024)
This research aims to analyze and describe the management of Scout extracurricular activities at SDIT Al-Mumtaz Pontianak, focusing on the aspects of planning, organizing, implementing, and supervising. The method employed is a case study approach within the qualitative research paradigm as proposed by Spradley. Data collection techniques encompass structured interviews, participatory observation, and documentary analysis. The findings indicate that the management of Scout extracurricular activities at Gudep 05.047-05.048 Umar bin Abdul Aziz Fatimah Az-Zahra Pangkalan SDIT Al-Mumtaz Pontianak can be outlined as follows: (1) Planning, involving mentor meetings at the beginning of each academic year to discuss activity plans; (2) Organization, where the Front Cluster leadership is held by Kamabigus, overseeing the male and female Gudep mentor leaders; (3) Implementation: Overall, the execution of Scout activities at SDIT Al-Mumtaz Pontianak reflects a unique approach and a strong commitment to Islamic values; (4) Supervision, carried out collaboratively by several parties, including mentors, coordinators, and the Deputy Head of Student Affairs.